Game Based Learning (GBL) as an innovative approach in social system learning: An experimental study at SMP Negeri 1 Balocci - Hudayah Sulaiman; Indriani Indriani; Ramdani Sidik; A Hardiyanti; Alwi Usra Usman (Priviet Social Sciences Journal, 2026)
This study examined the effectiveness of Game-Based Learning (GBL) as an innovative instructional approach for improving students’ understanding of social system concepts in Social Studies education. A quasi-experimental design employing a Non-Equivalent Control Group Design was used. The participants consisted of 30 eighth-grade students at SMP Negeri 1 Balocci, divided into an experimental group (n = 15) and a control group (n = 15). Data were collected through pretests, posttests, and classroom observations. The experimental group received instruction through Game-Based Learning activities, while the control group received conventional instruction. Data were analyzed using descriptive statistics, Shapiro–Wilk normality tests, Levene’s homogeneity test, Independent Samples t-test, and N-Gain analysis. The results revealed a significant difference between the two groups, with the experimental group achieving a higher posttest mean score (M = 90.75) than the control group (M = 72.20). The N-Gain score also indicated a higher level of learning improvement in the experimental group (0.78) compared with the control group (0.58). These findings suggest that Game-Based Learning effectively enhances students’ learning outcomes, engagement, and conceptual understanding of social systems. The study concludes that GBL is a promising pedagogical strategy for transforming abstract social studies concepts into meaningful and engaging learning experiences.